Composition and mineralization of organic compost derived from composting of fruit and vegetable waste - Motta Tratsch, Mauricio Vicente; Ceretta, Carlos Alberto; Souza da Silva, Leandro; Avelar Ferreira, Paulo Ademar; Brunetto, Gustavo (Revista Ceres, 2025)
Fruit and vegetable waste can be used for the production of organic compost, which when mineralized can increase the availability of nitrogen. The objectives of this study were: (a) to produce compost from different ratios of fruit and vegetable waste, rice husk and poultry manure that meets the legislation on organic fertilizers and (b) to assess the mineralization of N in substrates prepared with different ratios of compost. In experiment 1, the following treatments were prepared using (fruit and vegetable residue: rice husk: poultry waste) (v:v): Treatment 1 (2:1:0), T2 (1:1:1), T3 (1.5:1:0) and T4 (1.2:1:0). All the treatments were subjected to composting for 95 days, were subjected to analysis of nutrients, organic carbon, C/N, CEC/C, pH and moisture content. The composts were compared in regards to the parameters required by legislation. In experiment 2, the treatments consisted of eight blends of agricultural peat, carbonized rice husk and organic compost pre-selected from experiment 1. The NO3–N and NH+4-N contents were analyzed in the substrate at time zero and at 7, 14, 28, 56, 112 days after incubation. Compost (C2) met the parameters required by legislation and the use of 40% in the substrate composition promoted the mineralization of N.